Le dernier écho d’une symphonie - Philippe Dufour (Flaubert: Revue Critique et Génétique)
Music in Flaubert’s work is like the image of an unheard language going beyond social discourse and commonplaces. It is a non figural language inviting the audience to a dreaming listening. These theme and metaphor are considered here for their well-chosen modulations, but also for their disphoric effects. The theme enters eventually into consonance with the universe of incommunicability.